Value management implementation barriers for sustainable building: a bibliometric analysis and partial least square structural equation modeling - Kineber, A.F. (Emerald Group Holdings Ltd., 2021)
Purpose: The purpose of this paper is to examine the relationship between overcoming the value management (VM) implementation barriers and VM implementation in the Egyptian building sector. Design/methodology/approach: A critical review of the literature on VM was used to through bibliometric analysis has been conducted to highlight the studiesâ gap and establish the VM barriers. These obstacles were then contextually transformed via a semi-structured interview and a pilot study, and subsequently organized in the form of a theoretical model. The primary data was collected from 335 building stakeholders in Egypt through the administration of questionnaire surveys. Consequently, structural equation models of partial least squares were applied to statistically assess the final model of VM barriers. Findings: The bibliometric analysis shows that there is an inadequate study on VM implementation barriers in the Egyptian construction industry and insufficient studies on implementing VM in developing countries. Results obtained from the proposed model showed that overcoming the VM barriers has a major connection with successful VM implementation. This is indicated with the value of Ã = 0.743, which is necessary when the firm is overcoming 1 unit of VM barriers. Originality/value: This study fills the knowledge gap by identifying and emphasizing the critical obstacles to VM implementation. Â© 2021, Emerald Publishing Limited.